Pembagian Harta Bersama Pada Saham Pendirian Perseroan Terbatas - Lintang Fajarisya Setiawan (Scholar Center, 2022)
Divorcement of husband and wife does not necessarily terminate all matters between both divorced parties, there are legal consequences to be considered, one of which is joint property that must be shared. Positive law in Indonesia does not yet fairly regulate distribution of joint assets in shares of Limited Liability Companies in the Decision of the Supreme Court number 80/Pdt.G/2020/PN.JKT.UTR. Following the case above, the author is interested to discuss: (1) How is the distribution of joint assets in shares of the establishment of a limited liability company? (2) What are the Legal Consequences for the Distribution of Joint Assets to Limited Liability Company Shares? This study uses normative research methods. Several conclusions can be drawn from the results and discussion. First, in case the company is established by husband and wife then divorced, one of them must sell their shares to another person within 6 months, if after 6 months the shares have not been transferred to another person, all losses or legal consequences of the company is the responsibility of either husband or wife, and if there is an interested third party, they can apply for the company dissolution to the local District Court. Second, that the assets of a limited liability company established by husband and wife, any losses as long as the shareholder is a sole shareholder, will be the responsibility of the sole shareholder and borne by the assets of the shareholder. As legal protection provided by the law of limited liability company on the legal consequence is that each limited liability company shareholder becomes sole because of the reduction in the company's shareholder, then the law provides a period of 6 months to sell part of its shares to other parties.